Effect of Reserpine and Some Adrenolytics on the Anticoagulant Activity of Pelentan ( Ethylbiscoumacetate) - Hrdina, P; Kovalčík, V (Thrombosis and Haemostasis, 1967)
The interaction of varions drugs affecting adrenergenic system with the hypoprothrombinémie activity of coumarine derivative pelentan was studied in rats.Short-term pretreatment with reserpine almost completely inhibited the hypoprothrombinémie effect of pelentan given either orally or intravenously. The longterm pretreatment with reserpine caused, on the other hand, a marked increase of the anticoagulant activity of pelentan.Guanethidine, bretylium and a-methyldopa significantly increased the pelentan activity and such a tendency have shown some a-adrenergenic blocking drugs.Pharmacologically induced decrease in sympathetic transmitter function creats thus a situation which favours the anticoagulant activity of pelentan.Injection of noradrenaline was able to abolish the inhibitory or potentiating effect of short-term or long-term reserpine pretreatment on the hypoprothrombinémie activity of pelentan.